Multiple Personality Disorder in M. Night Shyamalan’s Split (2016) Movie Script - Mahaju, Kesia Nadia Renjelita; Wuntu, Ceisy N.; Oroh, Elisabeth Z. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The purpose of this study is to Multiple Personality Disorder mental disorder in Split (2016) by M. Night Shyamalan's film using defense mechanism theory. This research was qualitative research. This research used two data sources: primary data and secondary data. The primary data source was the Movie Script of this movie. Then, the secondary data sources were books, articles, journal references from the internet about the movie, and other sources that related to the researched. In analazyng the data the writer used Psychological Approach based on Theory of Sigmund Freud The Defense Mechanism. there are some types of the defense mechanism proposed by freud. and the result shows several types of defense mechanisms in Kevin's character with a split personality such as Repression, Reaction Formation, Projection, Regression, Sublimation, Denial, Rationalization, and Identification. Split uses various ego defense mechanisms as narrative tools to illustrate the psychological complexity of Kevin Wendell Crumb's character. Through this exploration, Shyamalan not only creates a deep and complex character, but also delves into themes of trauma, identity, and self-protection, giving a rich literary dimension to an intense and evocative story.